EFEKTIVITAS PERAWATAN LUKA MODERN DENGAN TEKNIK BALUTAN MOIST WOUND HEALING PADA PENYEMBUHAN ULKUS DIABETIKUM DI KLINIK RUMAT JAKARTA.: EFEKTIVITAS PERAWATAN LUKA MODERN DENGAN TEKNIK BALUTAN MOIST WOUND HEALING PADA PENYEMBUHAN ULKUS DIABETIKUM DI KLINIK RUMAT JAKARTA. - Henrianto Karolus Siregar; Yenny Yenny; Samsinar Butar; Santa Maria Pangaribuan; Khairunnisa Batubara (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah., 2023)
Diabetes Mellitus often becomes a serious health problem in various developing and developed countries in the world. Most people with diabetes mellitus are at risk of developing diabetic ulcers. If not treated quickly it can develop into an infection. The newest wound healing methods currently have an important role in treating diabetic ulcers, one of which is Modern Dressing with Moist Wound Healing. The aim of this research is to identify the effectiveness of modern wound care using moist wound healing dressing techniques in healing diabetic ulcers at the Rumat clinic in Jakarta. The research design used in this study used a quasi-experimental design with a cross-sectional method approach. The population in this study were all patients who underwent wound care at the Rumat Jakarta clinic. The sampling used was accidental sampling, which took cases or respondents who happened to be present or available in a place according to the research context, namely 30 respondents. Based on the results of the Paired T-Test and Independent T-Test, the p-value was obtained (0.000 < α 0.05), this proves that there is the effectiveness of modern wound care using the Moist Wound Healing dressing technique in healing diabetic ulcers in home clinics in Jakarta. Meanwhile, in the control group, after carrying out bivariate analysis using statistical tests, a significance value of p value α = 0.080 (p > 0.05) was obtained. Thus, it can be said that there is no effectiveness of modern wound care using moist wound healing dressing techniques in healing diabetic ulcers at the Rumat Clinic in Jakarta. It is hoped that the Jakarta Rumat Clinic can improve the quality and quality of modern wound care services using moist wound healing dressing techniques for diabetic ulcer sufferers.